Respiratory plasticity during acclimation to hypoxia and following a recovery in normoxia - Zhang Yangfan F; Mauduit Florian; Pettinau Luca; Ollivier Helene; Lancien Frederic; Anttila Katja; Farrell Anthony P; Claireaux Guy (CANADIAN SCIENCE PUBLISHING, 2025)
Phenotypic plasticity manifested after acclimatization is a very important source of biological variability among fish species. We hypothesized that hypoxic acclimation, besides potentially generating a temporary hypoxic respiratory phenotype, would also manifest as a continued benefit after reacclimation to normoxia. Hence, we holistically characterized the respiratory phenotype of European sea bass (Dicentrarchus labrax (Linnaeus, 1758)) acclimated to normoxia with or without prior acclimation to hypoxia. Compared with the original normoxic phenotype, prior acclimation to hypoxia and return to normoxia produced a 27% higher absolute aerobic scope (AAS), a 24% higher citrate synthase activity in red muscle, and a 28% lower excess post exercise O2 consumption. Additional testing of hypoxia-acclimated fish under normoxia explored the specific effects of hypoxic acclimation. The hypoxic phenotype, when compared with the original normoxic phenotype, had a lower standard metabolic rate, a better hypoxia performance, and a lower minimum PO2 for supporting 50% AAS. Thus, respiratory plasticity allows sea bass to improve its maximum aerobic capacity after returning to normoxia from hypoxic acclimation, a potential benefit from exploiting a hypoxic habitat. Given this respiratory malleability, general predictions for marine fish exploiting a more hypoxic future should better consider respiratory plasticity and prolonged effects of hypoxic exposures.